The impact of lockdowns and travel restrictions COVID 19 pandemics on glycaemic control of diabetic patients followed up at a tertiary care center from Northern Sri Lanka - Pravinson, M.; Ghetheeswaran, S.; Kumanan, T.; Aravindhan, M. (Sri Lanka Journal of Diabetes, Endocrinology and Metabolism, 2022)
Background Nationwide lockdown held in Sri Lanka about six months from February 2020, due to the COVID-19 pandemic. Patients with diabetes mellitus have faced difficulties and their routine care was compromised. The impact on diabetic care and determining factors during that period have not yet been examined. Objectives The primary objective of this study is to assess the glycaemic control of patients who are following tertiary care diabetic centre in Teaching Hospital Jaffna. Other objectives are the factors that could influence the sugar control during the lockdown period and describe any significant relationships. Design and setting A cross-sectional database study analysing 280 questionnaires from patients aged 16 and the above, who annually visiting to a designated diabetic clinic centre, Teaching Hospital, Jaffna from north part of Sri Lanka. Patients whoever had two values of serum HbA1C which must be both pre and post lockdown values, recruited to this study. Methodology An interviewer administrative questionnaire-based data collection performed under several categories. We assessed the temporal trends between changes of HbA1C and weight over one year. Results Among 280 patients of diabetes mellitus, female patients were 70.4%, and majority of patients were in age of 60 and more. Regarding diabetes, 277 patients had type 2 diabetes, and number of patients with oral drugs only was 88.9%. Drug compliance had been plumed during lockdown period significantly (p<0.001). Changes in mean HbA1c values between pre and post lockdown values were significant (t-6.061, p<0.001) but that of mean weight changes did not (t-1.786, p=0.075). Most patients received drugs adequately 98.6% and obtained medications from government sector 93.9%. Psychological and financial burdens did not influence in diabetic care. Conclusions Statistically significant changes have been observed in post-lockdown values of HbA1c and drug compliance compared to pre-lockdown values. This Covid-lockdown period did not affect the psycho-social-financial status of many patients. Effective government sector influenced drug delivery.
Keywords: HbAlc; Diabetes mellitus; Pre-lockdown period; Post-lockdown period